Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Produktivitas Kerja Dosen di Tangerang Selatan - Asep Suherman (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to examine the influence of work environment and job stress on the work productivity of lecturers in South Tangerang. The method used in this research is a quantitative method with a descriptive approach. The population of this study includes all lecturers working in higher education institutions in South Tangerang, with a sample determined using the saturation sampling technique. A total of 100 lecturers from several higher education institutions in South Tangerang were taken as samples in this study. Data were collected through observation, questionnaires, interviews, and documentation, then analyzed using multiple linear regression. The results show that the work environment and job stress have a significant effect on lecturers' work productivity. The coefficient of determination (R Square) of 0.825 indicates that 82.5% of the variation in lecturers' work productivity can be explained by the variables of work environment and job stress. A good work environment, including adequate physical facilities, positive interpersonal relationships, a supportive work culture, and effective administrative support, as well as good stress management, can increase lecturers' productivity. These findings provide recommendations for educational institution managers to create a conducive work environment and effective stress management strategies to enhance lecturers' productivity.